Comparative Analysis of The Influence of Liquidity, Solvency and Profitability on Stock Prices in Non Cylical Consumer Sector Manufacturing Companies Listed on The Indonesian Stock Exchange (BEI) For The 2018-2022 Period - Antonius Panji Santoso; Lia Rachmawati; Nurshadrina Kartika Sari (Medikun Publisher, 2024)
This research aims to analyze the influence of the variables liquidity ratio, solvency ratio, and profitability ratio on share prices with non-cyclical consumer sector manufacturing companies as research objects. This research was conducted over a period of five years, namely from 2018 to 2022 with a sample size of 19 companies. Sampling in this study used a purposive sampling technique and data was analyzed using multiple linear regression analysis. The research results show that partially the liquidity ratio and solvency ratio have no effect on stock prices, while the profitability ratio variable has an effect on stock prices. Simultaneously, the variables liquidity ratio, solvency ratio and profitability ratio have no influence on stock prices.